Convective mass transport dominates surfactant adsorption in a microfluidic Y-junction. Issue 44 (21st October 2016) - Muijlwijk, Kelly; Huang, Wenqian; Vuist, Jan-Eise; Berton-Carabin, Claire; Schroën, Karin
Abstract : Surfactant adsorption during emulsification can be quantified by measuring the acting interfacial tension using a Y-junction microfluidic device. Abstract : Surfactant adsorption during emulsification can be quantified by measuring the acting interfacial tension using a Y-junction microfluidic device. To obtain insight into the surfactant transport mechanism to the interface, the effect of shear force on the acting interfacial tension was assessed by systematically varying the continuous phase viscosity and velocity. Varying the continuous phase viscosity did not affect the acting interfacial tension, indicating that surfactant adsorption during Y-junction emulsification is not diffusion-limited. The acting interfacial tension was inversely dependent on the continuous phase velocity, which indicates that surfactant adsorption is governed by convective mass transfer resulting from the continuous phase velocity. The acting interfacial tension can be measured in the sub-millisecond time scale and under convective transport conditions using the Y-junction. These conditions are relevant to industrial emulsification and cannot be assessed by conventional tensiometry techniques ( e.g., drop tensiometers) where surfactant adsorption is mostly driven by diffusion. We believe, therefore, that this method can be used to understand emulsifier adsorption during industrial emulsification, which can, in turn, be used to rationally design emulsion formulations and processes.